The SRL peptide of rhesus rotavirus VP4 protein governs cholangiocyte infection and the murine model of biliary atresia. Issue 4 (10th January 2017) - Mohanty, Sujit K.; Donnelly, Bryan; Lobeck, Inna; Walther, Ashley; Dupree, Phylicia; Coots, Abigail; Meller, Jaroslaw; McNeal, Monica; Sestak, Karol; Tiao, Greg
Abstract : Biliary atresia (BA) is a neonatal obstructive cholangiopathy that progresses to end‐stage liver disease, often requiring transplantation. The murine model of BA, employing rhesus rotavirus (RRV), parallels human disease and has been used to elucidate mechanistic aspects of a virus induced biliary cholangiopathy. We previously reported that the RRV VP4 gene plays an integral role in activating the immune system and induction of BA. Using rotavirus binding and blocking assays, this study elucidated how RRV VP4 protein governs cholangiocyte susceptibility to infection both in vitro and in vivo in the murine model of BA. We identified the amino acid sequence on VP4 and its cholangiocyte binding protein, finding that the sequence is specific to those rotavirus strains that cause obstructive cholangiopathy. Pretreatment of murine and human cholangiocytes with this VP4‐derived peptide (TRTRVSRLY) significantly reduced the ability of RRV to bind and infect cells. However, the peptide did not block cholangiocyte binding of TUCH and Ro1845, strains that do not induce murine BA. The SRL sequence within TRTRVSRLY is required for cholangiocyte binding and viral replication. The cholangiocyte membrane protein bound by SRL was found to be Hsc70. Inhibition of Hsc70 by small interfering RNAs reduced RRV's ability to infect cholangiocytes. This virus‐cholangiocyte interaction is also seen in vivo in the murine model of BA, where inoculation of mice with TRTRVSRLY peptide significantly reduced symptoms and mortality in RRV‐injected mice. Conclusion : The tripeptide SRL on RRV VP4 binds to the cholangiocyte membrane protein Hsc70, defining a novel binding site governing VP4 attachment. Investigations are underway to determine the cellular response to this interaction to understand how it contributes to the pathogenesis of BA. (Hepatology 2017;65:1278‐1292)